EFFECT OF SOWING BY DIFFERENT SEEDING RATES ON QUALITATIV TTIATS OF FOUR WHEAT (Triticum aestivum L.) CULTIVAR SEEDS - & et al., Saudi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment was carried out at laboratories of Agriculture and Marshes College , University of Thi-Qar and at laboratories of agriculture  college , university of  Basra  during 2013 - 2014 . The aim of this study was to    identify the effect of the different seeding rates (80,100,120 and 140 kg.ha-1)  on viability and quality characters of  four wheat cultivars ( Abu-Ghraib, IPA – 99 , Al-fatih and Al-Iraq ) seeds . Factorial experiments in CRD was used with four replication in two factors . The results showed that there were significant differences between two factors of study and their interaction. The seeds produced  from seeding rate 80 kg.ha-1 gave the higher averages of field emergence , standard germination , radical length , seedling dry weight and protein percentage ( 81.18 % , 91.03 % , 7.92 cm , 5.23 gm and 13.71 % ), respectively . The seeds produced from  seeding rate 100 kg.ha-1  gave the higher averages  of  first count test and  plumule length ( 74.35 % and  6.45 cm ), respectively . The seeds produced from  seeding rate 120 kg.ha-1  gave the higher averages  of  carbohydrate percentage (61.27) . Al-Iraq seeds gave the higher averages of  field emergence , first count test  , standard germination , radical length , plumule length , seedling dry weight and  carbohydrate percentage ( 86.23% , 72.68 % , 93.22% , 8.51 cm , 6.88 cm , 5.83 gm and 61.65% ) , respectively. Abu-Ghraib seeds gave the higher averages of  protein percentage (13.94 ). Al-Iraq seeds  produced from  seeding  rate 80 kg.ha-1 gave the higher averages of  field emergence ,  radical length and seedling dry weight ( 89.14% , 8.87 cm and 6.65 gm ), respectively . Al-Iraq seeds that  product from  seed rate 100 kg.ha-1 gave the higher averages of first count test  , standard germination and plumule length ( 79.00% , 95.98% and 7.83 cm ), respectively . Al-Iraq seeds that  product from  seed rate 120 kg.ha-1 gave the higher averages of carbohydrate percentage ( 61.92% ). Abu-Ghraib seeds  that  product  from  seed rate 100 kg.ha-1 gave the higher average of protein percentage(14.25).